Endoparasites and vector-borne pathogens in dogs from Greek islands: Pathogen distribution and zoonotic implications. - Anastasia Diakou; Angela Di Cesare; Simone Morelli; Mariasole Colombo; Lenaig Halos; Giulia Simonato; Androniki Tamvakis; Frederic Beugnet; Barbara Paoletti; Donato Traversa (Public Library of Science (PLoS), 2019)
The present study investigated the presence of endo- and ecto-parasites, and vector-borne pathogens, in dogs from four islands of Greece. A total of 200 (123 owned and 77 sheltered) dogs were examined with different microscopic, serological and molecular methods. Of the examined dogs, 130 (65%) were positive for one or more parasites and/or vector-borne pathogens. The most common zoonotic intestinal helminths recorded were Ancylostomatidae (12.5%) and Toxocara canis (3.5%). Ninety-three dogs (46.5%) seroreacted to Rickettsia conorii. Twenty-two (11%) of them were also PCR positive and 7 (3.5%) showed corpuscles suggestive of Rickettsia spp. on the blood smears. Nineteen dogs (9.5%) were seropositive for Ehrlichia canis, three of them being also PCR positive. Dogs positive for Anaplasma phagocytophilum-Anaplasma platys (1%), Dirofilaria immitis (0.5%) and Babesia canis (0.5%) were also found. Fleas and ticks were recorded in 53 (26.5%) and 50 (25%) dogs, respectively, and all specimens were identified as Ctenocephalides felis felis and Rhipicephalus sanguineus sensu lato. Binary multiple univariate Generalized Linear Models were used to investigate factors and clinical signs related to the recorded positivity, while the association of specific signs with the pathogens was evaluated using tests of independence. Knowledge of occurrence and impact of zoonotic parasites and vector-borne pathogens in dog populations is crucial to prevent the infection in animals and people, and to control the risk of spreading of these pathogens in endemic and non-endemic areas.